Phase formation, microstructure and electrical properties of Ba0.9Ca0.1TiO3 ceramics fabricated via the solid-state combustion technique. Issue 1 (10th December 2022) - Sonchaopri, Nutkamon; Bhupaijit, Pamornnarumol; Yotthuan, Surirat; Sinkruason, Thanapon; Premwichit, Pathit; Suriwong, Tawat; Sumang, Rattiphorn; Vittayakorn, Naratip; Bongkarn, Theerachai
Abstract: In this research, the effects of calcination temperature in a range of 1050–1200 °C for 2 h and sintering temperature in a range of 1325-1400 °C for 2 h on phase formation, microstructure and electrical properties of lead-free Ba0.9 Ca0.1 TiO3 (BCT) ceramics fabricated via the solid-state combustion technique were investigated. For the XRD result, all the ceramics exhibited a coexisting phase between tetragonal and orthorhombic. The ceramic grain size tended to increase with increase of the sintering temperature. For BCT ceramic produced by the optimum sintering temperature (1375 °C for 2 h), the dielectric, ferroelectric and piezoelectric properties of ε C =7393, P r =7.60 μC/cm 2, E C =5.99 kV/cm and d 33 =158 pC/N, respectively, were obtained.